Morphometrics of selected forest babbler species and genetic variations of Black-capped Babbler [Pellorneum capistratum, (Temminck, 1823)] in Peninsular Malaysia - Abdl Jalil, Norehan (2019)
Babblers is one of the largest groups of insectivorous birds in Malaysian tropical rainforest with a high level of sympatry and morphological variations. Most babblers are short-distanced flyers and restricted to the interior forest, making them suitable candidate for biogeographic studies. Forest babblers are sensitive to forest disturbance due to their high habitat specificity and poor dispersal ability. Despite being common in lowland tropical forests, information on the morphological and genetic variations of the forest babblers in Malaysia are still lacking. Thus, this study was conducted to examine the morphometric variations of three forest babblers, namely the Black-capped Babbler (Pellorneum capistratum), Short-tailed Babbler (P. malaccense), and Chestnut-winged Babbler (Cyanoderma erythropterum) and further investigated the genetic variations of Black-capped Babbler populations from four sampling sites in Peninsular Malaysia. The main objective of this study was to elucidate the morphometric variations of these species in order to understand their ecological adaptations and functions in the forest habitats. The specific objectives were to develop a set of morphometric measurements using discriminant function analysis (DFA) which can be used for direct sex determination of these babbler species in the field. Genetic study of Black-capped Babbler was conducted to determine the genetic variations and connectivity of Black-capped Babbler populations in Peninsular Malaysia using double digest Restriction-site Associated DNA Sequencing (ddRAD-Seq). Eighty-six individuals comprising 22 Black-capped Babbler, 32 Short-tailed Babbler, and 32 Chestnut-winged Babbler were captured at Sungai Lalang Forest Reserves and Taman Botani Negara Shah Alam in Selangor, Panti Forest Reserves in Johor, and Bintang Hijau Forest Reserves in Perak. Based on seven morphometric traits taken from each species, results from DFA suggest that head and tail lengths can be used to distinguish the sexes of the Short-tailed Babbler with 73.3 % accuracy. For the Chestnut-winged Babbler, it was wing lengths and weight with 82.8 % accuracy. However, the DFA was not conducted for the Black-capped Babbler due to small sample size for females. Based on canonical function plots for Short-tailed and Chestnut-winged Babblers, there is no difference in morphometric measurements for all individuals at four sampling sites. However, for Black-capped Babbler, all individuals were separated morphologically based on sampling sites. Genetic analysis of 21 individuals of the Black-capped Babbler revealed high genetic connectivity among individuals based on the sampling sites. Based on Admixture analysis (k=1), all the 21 individuals were assigned into one putative population, indicating that most individuals were descended from closely related ancestor. However, based on morphometric data, it is shown that there is a small difference in morphology according to sampling sites. Netview analysis using k=4 showed that each individual in a population were clearly grouped bases on sampling sites. Overall, this study provides an easy and reliable method to facilitate direct sex determination for three babbler species in field, as well as revealing the population genetic structure of the Black-capped Babbler in Malaysia. Such information is crucial for the management and conservation of forest bird species in Malaysia and Southeast Asia.